Determining the Shortest Path for Souvenir Delivery to Tourist Attractions in Pamekasan Using Excel Solver - Badrud Tamam; Motik Arisca Dyana (Yayasan Adra Karima Hubbi, 2023)
Pamekasan, as one of the districts in East Java, is famous for its various interesting tourist attractions. As the number of tourists increases, the need for typical Pamekasan souvenirs also increases. This encourages souvenir craftsmen to look for efficient ways to distribute their products to tourist attractions. One method that can be used is to use Solver Excel to determine the shortest path for sending souvenirs. This research aims to determine the shortest path for sending souvenirs from production sites to tourist attractions in Pamekasan using Solver Excel. The research method used is quantitative using Excel Solver. The data used is data on the distance between production sites and tourist attractions in Pamekasan. This data was obtained from the Pamekasan Regency Tourism and Culture Office. The research results show that Solver Excel can be used to determine the shortest route for sending souvenirs from production sites to tourist attractions in Pamekasan so that it can help souvenir craftsmen to save time and costs in distributing their products.